Town of Maple Grove comprehensive planning public opinion survey report, 2008 - Hadley, Shelly; Trechter, David (My University, 2009)
The purpose of this survey was to understand public opinions about a range of important land use issues facing the Town of Maple Grove in Barron County. Survey results will provide input into the comprehensive land use plan for the town.
39 p.
Keywords: Survey; University of Wisconsin-River Falls. Survey Research Center; UWRF Survey Research Center Report; Public opinion survey; Community planning; Comprehensive plan report; Comprehensive plan; Town of Maple Grove comprehensive plan; Barron County, Wisconsin; Barron County (Wis.); Town of Maple Grove; Maple Grove (Barron County, Wis. : Town); Maple Grove (Barron County, Wis. : Town)--Surveys; Public opinion--Wisconsin--Maple Grove (Barron County : Town); Land use--Wisconsin--Maple Grove (Barron County : Town); City planning--Wisconsin--Maple Grove (Barron County : Town)